Computational fluid dynamics simulations of single-phase flow in a filter-press flow reactor having a stack of three cells. (20th October 2016) - Sandoval, Miguel A.; Fuentes, Rosalba; Walsh, Frank C.; Nava, José L.; de León, Carlos Ponce
Graphical abstract: Highlights: Computational fluid dynamic simulations in a filter-press stack of three cells. The fluid velocity was different in each cell due to local turbulence. The upper cell link pipe of the filter press cell acts as a fluid mixer. The fluid behaviour tends towards a continuous mixing flow pattern. Close agreement between simulations and experimental data was achieved. Abstract: Computational fluid dynamics (CFD) simulations were carried out for single-phase flow in a pre-pilot filter press flow reactor with a stack of three cells. Velocity profiles and streamlines were obtained by solving the Reynolds-Averaged Navier-Stokes (RANS) equations with a standard k − ε turbulence model. The flow behaviour shows the appearance of jet flow at the entrance to each cell. At lengths from 12 to 15 cm along the cells channels, a plug flow pattern is developed at all mean linear flow rates studied here, 1.2 ≤ u ≤ 2.1 cm s −1 . The magnitude of the velocity profiles in each cell was different, due to the turbulence generated by the change of flow direction in the last fluid manifold. Residence time distribution (RTD) simulations indicated that the fluid behaviour tends towards a continuous mixing flow pattern, owing to flow at the output of each cell across the upper cell link pipe, which acts as a mixer. Close agreement between simulations and experimental RTD was obtained.